Diversity and Function of Capsular Polysaccharide in Acinetobacter baumannii - Singh, Jennifer K.; Adams, Felise G.; Brown, Melissa H. (Frontiers in Microbiology, 2019)
The Gram-negative opportunistic bacterium Acinetobacter baumannii is a significant cause of hospital-borne infections worldwide. Alarmingly, the rapid development of antimicrobial resistance coupled with the remarkable ability of isolates to persist on surfaces for extended periods of time has led to infiltration of A. baumannii into our healthcare environments. A major virulence determinant of A. baumannii is the presence of a capsule that surrounds the bacterial surface. This capsule is comprised of tightly packed repeating polysaccharide units which forms a barrier around the bacterial cell wall, providing protection from environmental pressures including desiccation and disinfection regimes as well as host immune responses such as serum complement. Additionally, capsule has been shown to confer resistance to a range of clinically relevant antimicrobial compounds. Distressingly, treatment options for A. baumannii infections are becoming increasingly limited, and the urgency to develop effective infection control strategies and therapies to combat infections is apparent. An increased understanding of the contribution of capsule to the pathobiology of A. baumannii is required to determine its feasibility as a target for new strategies to combat drug resistant infections. Significant variation in capsular polysaccharide structures between A. baumannii isolates has been identified, with over 100 distinct capsule types, incorporating a vast variety of sugars. This review examines the studies undertaken to elucidate capsule diversity and advance our understanding of the role of capsule in A. baumannii pathogenesis.